2014
DOI: 10.1007/s00213-014-3435-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection by the synthetic neurosteroid enantiomers ent-PREGS and ent-DHEAS against Aβ25–35 peptide-induced toxicity in vitro and in vivo in mice

Abstract: Rationale PREGS and DHEAS are pro-mnesic, anti-amnesic and neuroprotective steroids in rodents. In Alzheimer's disease (AD) patient brains, their low concentrations are correlated with high levels of Aβ and tau proteins. The unnatural enantiomer ent-PREGS enhanced memory in rodents. We investigated here whether ent-PREGS and ent-DHEAS could be neuroprotective in AD models. Objective The effects of PREGS, ent-PREGS, DHEAS and ent-DHEAS against Aβ25-35 peptide-induced toxicity were examined in vitro on B104 ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…One study indicated that it did not have any effect on the Aβ 25–35 -induced decrease in PC12 cell viability [ 77 ]. More recently, we observed that it significantly and dose-dependently counteracted the reduced cell viability induced by Aβ 25–35 in rat B104 neuroblastoma cells by preventing the cells from entering late apoptosis [ 78 ]. DHEAS was also capable of significantly attenuating Aβ 25–35 -induced toxicity, by preventing the cells from entering both late apoptosis and necrosis [ 78 ] ( Figure 4 A)].…”
Section: Protective Effects Of Neuroactive Steroids On Ad-like Neumentioning
confidence: 99%
“…One study indicated that it did not have any effect on the Aβ 25–35 -induced decrease in PC12 cell viability [ 77 ]. More recently, we observed that it significantly and dose-dependently counteracted the reduced cell viability induced by Aβ 25–35 in rat B104 neuroblastoma cells by preventing the cells from entering late apoptosis [ 78 ]. DHEAS was also capable of significantly attenuating Aβ 25–35 -induced toxicity, by preventing the cells from entering both late apoptosis and necrosis [ 78 ] ( Figure 4 A)].…”
Section: Protective Effects Of Neuroactive Steroids On Ad-like Neumentioning
confidence: 99%
“…There is some support for this theory, albeit in a different disease context. Evidence suggests declining concentrations of neurosteroids, such as DHEA and DHEAS, are closely associated with increased risk of Alzheimer's disease (AD) (Wojtal et al 2006, El Bitar et al 2014. STS inhibition attenuated cognitive deficits in spatial learning and memory and in hippocampal synaptic plasticity in rats with amyloid β protein-induced AD (Yue et al 2016).…”
Section: Steroid Sulfation Pathways the Brain And Behaviormentioning
confidence: 99%
“…The mechanistic pathway that underlying the behavioral and electrophysiological effects of DU-14 is closely associated with the increased DHEAS. According to previous studies, up-regulation of DHEAS in the brain could: 1) block Aβ1-42 induced intracellular calcium overload (Kato-Negishi and Kawahara, 2008); 2) increase the production of growth factors (Luppi et al, 2009) and enhance brain cholinergic function (Dong and Zheng, 2012); 3) play an immunomodulatory role on NK functional activity in physiological aging and AD (Solerte et al, 1999); 4) have an antiglucocorticoid activity and neuroprotective effects, while its levels decreased in AD (Murialdo et al, 2001); 5) prevent the cells from entering late apoptosis and necrosis and stimulate neurite outgrowth per se (El Bitar et al, 2014); 6) protect hippocampal neurons against glutamate through elevating a kappaB-dependent transcription factor activity (Leskiewicz et al, 2008;Mao and Barger, 1998). Of course, a further investigation on the effects of DU-14 and its mechanisms in AD transgenic animals or AD patients would be urgently required in the future.…”
Section: Disscussionmentioning
confidence: 99%
“…Neuroactive steroids, either synthesized de novo in the nervous tissue or in the peripheral endocrine glands or as synthetic steroids, have exhibited multiple important modulatory effects on brain functions and diseases (Zheng, 2009). It is reported that the declining of some neuroactive steroids, such as dehydroepiandrosterone (DHEA) and dehydroepiandrosterone sulfate (DHEAS) are closely associated with the increased risk of AD and reduced neuroprotection (El Bitar et al, 2014;Taylor et al, 2014;Wojtal et al, 2006).…”
Section: Introductionmentioning
confidence: 99%